Referibilidade nas contribuições - Barichello, Fabio Basso (2008)
The objective of this dissertation is to establish a concept of referibilidade , in order to demonstrate whether it is an essential element of the contribution that helps defining the possible group of its taxpayers and, from the formulation of this concept, it aims to propose some thought about it. In order to do so, we have systematized the meanings of the word referibilidade which has been used in many ways in national jurisprudence and doctrine, and from them, we have tried to put up our own concept. We have observed that the referibilidade has constitutional status, representing an essential element of contributions which restricts the scope of tax jurisdiction for the personal criteria of rule-matrix of tax incidence, determining the necessary link between the group of taxpayers and the purpose of taxation. It also appeared to us that the material criteria of rule-matrix of tax incidence is not a specific state action, nor any advantage or special benefit. In fact, the state action is a result of the relationship of cause and consequence that is established between the purpose of taxation and the destination of the money collected by the State. The advantage or special benefit in relation to a particular group of taxpayers appears to be only an accidental element of the taxation. We have also found that in order to be considered a contribution, beyond the legal destination of the collected tax; there must be an effective allocation of the product collected for that purpose, meaning that this allocation was originally established. According to that, we have found out that referibilidade will be analyzed not only by the time the legislature acts are published creating the contribution, but also even after the termination of the tax credit, notably over the allocation of the collected taxes, by means that if any deviation occurs, the referibilidade will be affected as will be the validity of the contribution